Interpretation of uroflow curves: A global survey measuring inter and intra rater reliability. Issue 2 (27th January 2020) - Netto, Jose M. B.; Hittelman, Adam; Lambert, Sarah; Murphy, Kaitlyn; Collette‐Gardere, Therese; Franco, Israel
Abstract: Introduction: There is a large amount of intra and inter observer variability in defining curve shapes. This study aims to evaluate inter and intra rater reliability (RR) on evaluating uroflow curves in a broad spectrum of international practitioners. Methods: Eight hundred sixty‐four questionnaires were sent by email to health professionals that care for children with voiding dysfunction. It included demographic questions and 11 different uroflow curves and two duplicates. Results: Four hundred forty‐one emails were opened and 29.5% of those responded. Seventy percent of responders were physicians, including 46% pediatric urologists. Europe, South America, North America, Oceania, and Asia represented respondents. For the repeated bell smooth curve the intra rater agreement was 82.1% utilizing the International Children's Continence Society (ICCS) classification and 92.3% for the shape of the curve (bell, plateau, and tower [BPT]) ( P = .04). For the repeated interrupted plateau curve it was 69.5% and 97.5% for ICCS and for the continuity of the curve (smooth or fractionated [SF]) classifications, respectively ( P < .001). The curves were then divided into two groups for evaluation of inter RR. For the set of seven smooth curves, the inter RR was low in all classifications with α = .282, .497, and .242 for ICCS, SF, and BPT, respectively. The group of six fractionated curves showed a slightly better agreement with α = .533, .404, and .662 for ICCS, SF, and BPT, respectively. Conclusions: This is the largest study looking at inter and intra RR of uroflows in a disparate population of readers. It was evident from our findings that inter RR was poor and additionally intra RR was equally poor, indicating the unreliability of uroflow shapes to be used for research purposes.